Successful every-other-day liothyronine therapy for severe resistance to thyroid hormone beta with a novel THRB mutation; case report. Issue 1 (December 2016) - Maruo, Yoshihiro; Mori, Asami; Morioka, Yoriko; Sawai, Chihiro; Mimura, Yu; Matui, Katsuyuki; Takeuchi, Yoshihiro
Abstract Background Resistance to thyroid hormone beta (RTHβ) is a rare and usually dominantly inherited syndrome caused by mutations of the thyroid hormone receptor β gene (THRB ). In severe cases, it is rarely challenging to control manifestations using daily therapeutic replacement of thyroid hormone. Case presentation The present case study concerns an 8-year-old Japanese girl with a severe phenotype of RTH (TSH, fT3, and fT4 were 34.0 mU/L, >25.0 pg/mL and, >8.0 ng/dL, respectively), caused by a novel heterozygous frameshift mutation in exon 10 of the thyroid hormone receptor beta gene (THRB ), c.1347-1357 del actcttccccc : p.E449DfsX11. RTH was detected at the neonatal screening program. At 4 years of age, the patient continued to suffer from mental retardation, hyperactivity, insomnia, and reduced resting energy expenditure (REE), despite daily thyroxine (L-T4) therapy. Every-other-day high-dose liothyronine (L-T3) therapy improved her symptoms and increased her REE, without thyrotoxicosis. Conclusion In a case of severe RTH, every-other-day L-T3 administration enhanced REE and psychomotor development, without promoting symptoms of thyrotoxicosis. Every-other-day L-T3 administration may be an effective strategy for the treatment of severe RTH.